Reduction in the Cesarean Delivery Rate After Obstetric Care Consensus Guideline Implementation. Issue 1 (July 2016) - Wilson-Leedy, Jonas G.; DiSilvestro, Alexis J.; Repke, John T.; Pauli, Jaimey M.
Abstract : OBJECTIVE: To evaluate the rate of primary cesarean delivery after adopting labor management guidelines. METHODS: This is a before–after retrospective cohort study at a single academic center. This center adopted guidelines from the Consensus for the Prevention of the Primary Cesarean Delivery. Nulliparous women attempting vaginal delivery with viable, singleton, vertex fetuses were included. For the primary outcome of cesarean delivery rate among induced or augmented patients, 200 consecutive women managed before guideline adoption were compared with 200 similar patients afterward. Secondary outcomes of overall cesarean delivery rate, maternal morbidity, neonatal outcomes, and labor management practices were analyzed with inclusion of intervening spontaneously laboring women. RESULTS: Between September 13, 2013, and September 28, 2014, 275 women preguideline and 292 postguideline were identified to include 200 deliveries after induction or augmentation each. Among women delivering after induction or augmentation, the cesarean delivery rate decreased from 35.5% to 24.5% (odds ratio [OR] 0.59, 95% confidence interval [CI] 0.38–0.91). The overall cesarean delivery rate decreased from 26.9% to 18.8% (adjusted OR 0.59, CI 0.38–0.92). Composite maternal morbidity was reduced (adjusted OR 0.66, CI 0.46–0.94). The frequency of cesarean delivery documenting arrest of dilation at less than 6 cm decreased from 7.1% to 1.1% postguideline (n=182 and 176 preguideline and postguideline, respectively, P =.006) with no change in other indications. CONCLUSION: Postguideline, the cesarean delivery rate among nulliparous women attempting vaginal delivery was substantially reduced in association with decreased frequency in the diagnosis of arrest of dilation at less than 6 cm. Abstract : Supplemental Digital Content is Available in the Text.After adopting consensus guidelines for prevention of primary cesarean delivery, reduced diagnosis of labor arrest is associated with a decrease in the cesarean delivery rate among nulliparous women.